Influence of Tanshinone IIA on apoptosis of human esophageal carcinoma Eca‐109 cells and its molecular mechanism. Issue 4 (13th April 2017) - Zhang, Yan; Li, Shan; He, Hang; Han, Qianqian; Wang, Baiyan; Zhu, Yanqin
Abstract : Background: Previous studies have shown that Tanshinone (Tan) IIA exerts obvious antitumor efficacy; however, its molecular mechanism remains unclear. This study was conducted to identify the influence of Tan IIA on Eca‐109 cell apoptosis, explore its molecular mechanism, and provide a theoretical basis for clinical application. Methods: Eca‐109 cells were cultured in vitro and treated with different concentrations of Tan IIA. Morphologic changes were viewed under inverted fluorescence microscope with dual acridine orange/ethidium bromide staining assay. Methyl‐thiazolyl‐tetrazolium and Annexin V propidium iodide assays were respectively used to measure cell viability and apoptosis rate. The protein and messenger (m)RNA expression of binding immunoglobulin protein (BIP), mitochondrial cytochrome c (CytC), and caspase‐9 were detected by Western blot and quantitative real‐time PCR, respectively. Results: Cell viability decreased and the apoptosis rate significantly increased with increasing concentrations of Tan IIA (0, 20, 40, 60 μg/mL), which indicated that Tan IIA inhibited the proliferation and induced the apoptosis of Eca‐109 cells in a dose‐dependent manner. Eca‐109 cells treated with 60 μg/mLTan IIA showed typical morphological changes of apoptosis under the inverted microscope. Moreover, compared with the negative control group, protein and mRNA expression of BIP decreased significantly ( P  < 0.05), whereas protein and mRNA expression of CytC and caspase‐9 increased significantly ( P  < 0.05). Conclusion: Tan IIA can induce apoptosis in human esophageal carcinoma Eca‐109 cells by regulating BIP, CytC, and caspase‐9 expression. Endoplasmic reticulum stress and mitochondrial‐dependent may be involved in Tan IIA‐induced Eca‐109 cell apoptosis.